Case Report: High burdens of air sac worms (Diplotriaena sp.) in three northern flickers (Colaptes auratus) and a pileated woodpecker (Dryocopus pileatus) - Freeman, Alyssa R.; Sullivan-Brugger, Lyndon E.; Groves, Bethany; Rosenhagen, Nicki; Garrett, Kayla B.; Yabsley, Michael J. (Frontiers in Parasitology, 2025)
Diplotriaena spp. are nematode parasites of the abdominal and thoracic air sacs of numerous avian species worldwide. Dipoltriaena infections are generally subclinical, but high worm burdens can lead to morbidity and mortality. In this case series, Diplotriaena were recovered from a pileated woodpecker (Dryocopus pileatus) in 2017 and three northern flickers (Colaptes auratus) in 2023 and 2024 from Washington, USA. All four presented to a wildlife rehabilitation center with either respiratory signs or trauma with varied severity. A large number of worms (>44 worms) were surgically removed from the pileated woodpecker. The bird improved and was subsequently released. All three northern flickers were humanely euthanized due to poor prognosis and worsening conditions. Nematodes from Cases 1 and 4 were identified as a Diplotriaena sp. but they did not match any described species. Ethanol-fixed worms were available from one flicker case for genetic characterization. Partial 18S rRNA sequences (888bp) from two worms from a flicker were identical and 98-98.5% similar to numerous Diplotriaena obtusa sequences. The sample Diplotriaena sp. grouped separately from the three closest matches in the GenBank database, Diplotriaena anthreptis and two clades of Diplotriaena obtusa and Diplotriaena bargusinica. The partial COI sequences (674bp) were identical to each other and 80-85% similar to numerous Spiruromorpha representatives. Due to a lack of available samples in the GenBank database and incomplete morphological descriptions of the genus, identification to species was not possible. In summary, all four cases in this case series occurred in free-ranging birds in Washington state and represented unusually high burdens of Diplotriaena sp. We believe that the high worm burden contributed to trauma, respiratory pathology, and weight loss. Additional surveillance is needed to determine the prevalence and impact of this parasite on woodpecker populations and to more accurately identify the parasite species in these two species of woodpeckers.